Quality and Technological Properties of Gluten-Free Biscuits Made with Pachyrhizus ahipa Flour as a Novel Ingredient - Doporto, María Cecilia (2017)
The development of gluten-free foodstuffs with high nutritional quality components is an important objective to achieve. Pachyrhizus ahipa is one of the few leguminous species that produce edible tuberous roots with high nutritional value. Thus, the aim of this work was to formulate biscuits containing corn starch and 125 - 350 g・kg−1 of P. ahipa flour (AF) and to study the main physicochemical properties related to their nutritional and technological quality as well as their sensory acceptability. The formulation containing 250 g of AF kg−1 was selected for improving the product nutritional quality (i.e. higher protein content) without an extensive modification of textural properties. A formulation replacing corn starch by cassava flour (250 g・kg−1) was also analyzed. In this case, ahipa and cassava biscuits showed maximum force and energy required to bite twice and three times higher than the control, respectively. Slight variations were observed in color (DE and browning index). The overall acceptability of biscuits formulated with both flours was better scored than the control by a sensory panel. Principal component analysis allowed to relate quality attributes, chemical composition, and sensory characteristics of biscuits containing cassava or ahipa flours. The results indicated that ahipa flour could satisfactorily substitute part of the corn starch used in the formulations of gluten-free biscuits.